Students' Perceptions Of The Full-Day School Application: Its Relationship Toward Science Learning Motivation - Damopolii, Insar; Wambrauw, Hengky L.; Mutmainah, Siti (Jurnal Pendidikan dan Pengajaran, 2021)
Students' perceptions about full-day school (FDS) on student learning motivation have been widely studied. However, the relationship found is moderate. Moreover, its relationship with science learning motivation has not been optimally studied. The research paper was aimed to reveal the relationship between students' perceptions of full-day school and motivation to learn science. The correlational method was used in this research. Respondent was 87 learners taken from an Islamic Junior high school in Manokwari. Validated questionnaires were used to measure perception and motivation. Simple regression was used to calculated data. The findings showed that P <0.5, rxy = 0.726, and R square = 0.527. The findings reveal a strong relationship between students' perceptions of FDS on motivation to learn science. The application of FDS in schools has contributed to the students’ motivation to learn science. Scheduling science learning needs to consider motivating students to learn in science.